Microbiological and chemical characterization of traditional cheese made from milk produced by the Algarvian goat breed - Ratao, Isabel Maria Carneiro (Cranfield University, 2010)
This study was concerned with a chemical and microbiological characterisation of cheese made using milk from Algarvian goat breed. Seasonal variation of the microbiota and the gross chemical composition of the raw and boiled milk and cheese during the lactation period were studied. The cardoon microbiota and the variation of microbiota during ripening were studied also. The lactic acid bacteria (LAB) were isolated, identified to genus level and their technological properties such as bacteriocin production, acidifying capacity, proteolysis and lipolysis were studied. The results showed that boiling milk does not represent a cause of variation in its gross composition and almost all the gross components of the milk and cheese register no variation during the studied period, except for fat, which increased until the middle of the lactation period and decreased after that. In cardoon, the microorganisms that are able to produce spores are the most important, thus analysis of yeasts and moulds was carried out which allowed the arrangement of the tested samples into three groups. Most of the identified moulds from the cardoon samples are from the genus Aspergillus. During the study period, differences in the microbiota of the raw milk were not observed, with Lactococcus and Lactobacillus being the prevalent groups. All the tested microorganisms increased approximately by two orders of magnitude from milk to cheese. Lactobacillus was the predominant group during the maturation period. Total coliforms tended to diminish in the early stages of ripening. Isolates from Lactobacillus and Pediococcus genera showed fast acidification capacity, which could be an indicator of good potential for their use as starter bacteria. Some Lactobacillus produced bacteriocin which can contribute to the removal of other bacteria. Aerococcus, Leuconostoc and Lactobacillus presented high proteolytic activity, which mean they could be used as adjunct cultures to improve proteolysis. Only one isolate (Pediococcus) showed lipolytic activity. In conclusion, by their technological characteristics some isolates could be selected as starter cultures, however, further research of their pathogenesis is necessary before using them in pilot plant production.